Pengaruh Model Problem Bassed Learning Berbantuan Media Audio Visual Terhadap Keterampilan Memproduksi Teks Ceramah - Hestika; Nursaid; Hendri, Bunga Febrimora (Journal of Practice Learning and Educational Development, 2023)
There are three purposes of this research. First, describe the skills of producing lecture texts for class XI students of SMA Negeri 2 Pariaman before applying the Problem Based Learning (PBL) Model with Audio Visual Media Assistance. Second, describe the skills of producing lecture texts for class XI students of SMA Negeri 2 Pariaman after applying the Problem Based Learning (PBL) Model with Audio Visual Media Assistance. Third, analyze the effect of applying the Problem Based Learning (PBL) Model with Audio Visual Media Assistance on the skills of producing lecture texts for class XI students of SMA Negeri 2 Pariaman. This type of research is quantitative research. The research method applied is descriptive analysis method. The procedures of this research are: (1) pretest, (2) treatment, and (3) posttest. The population in this study were students of class XI SMA Negeri 2 Pariaman who were registered in the 2018/2019 school year as many as 258 students. The sample in this study were students of class XI IPA-5, totaling 30 students. Based on the results of data analysis found. First, the skills of producing lecture texts for class XI IPA-5 students of SMA Negeri 2 Pariaman before the implementation of the Problem Based Learning (PBL) Model with Audio Visual Media Assistance were in almost sufficient qualifications (55,57). Second, the skills of producing lecture texts for class XI IPA-5 students of SMA Negeri 2 Pariaman after the implementation of the Problem Based Learning (PBL) Model Assisted by Audio Visual Media are in good qualifications (77.97). Third, there is an effect of applying the Problem Based Learning (PBL) Model Assisted by Audio Visual Media on the skills of producing lecture texts for class XI IPA-5 students of SMA Negeri 2 Pariaman after the t-test at level 0.95, obtained tcount > ttable or 5.68 > 1.70.